2013
DOI: 10.1007/s12160-013-9570-y
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Disparities in Heterosexual and Sexual Minority Youth Ages 12–22 Years Old: Roles of Childhood Gender Nonconformity and Athletic Self-Esteem

Abstract: Background Physical activity is an important health determinant. Little is known about sexual orientation differences in physical activity and their psychosocial determinants. Purpose To examine adolescent and young adult hours/week of moderate/vigorous physical activity (MVPA) and team sports participation by sexual orientation and investigate contributions of gender nonconformity and low athletic self-esteem to possible sexual orientation differences. Methods Analysis of data from 5,272 males and 7,507 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
106
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 51 publications
11
106
1
1
Order By: Relevance
“…Evidence is accumulating that these messages carry with them health risks in myriad domains. [9][10][11][12]32 With the present study, it is clear that conformity to masculinity ideals confers risk of elevated BMI in both sexes and, for males in particular, more rapid BMI gains in adolescence. While our study examined a wide range of known predictors of BMI in youth, our results indicated that these exposures accounted for a relatively small proportion of the pronounced gender-expression group differences in BMI.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Evidence is accumulating that these messages carry with them health risks in myriad domains. [9][10][11][12]32 With the present study, it is clear that conformity to masculinity ideals confers risk of elevated BMI in both sexes and, for males in particular, more rapid BMI gains in adolescence. While our study examined a wide range of known predictors of BMI in youth, our results indicated that these exposures accounted for a relatively small proportion of the pronounced gender-expression group differences in BMI.…”
Section: Discussionsupporting
confidence: 50%
“…21 Furthermore, recent evidence implicates societal pressures on young people to conform to socially accepted expressions of masculinity and femininity in a range of health damaging behaviors, 9-11 including weightrelated behaviors. 11,12,32 Nevertheless, to our knowledge, this is the first prospective cohort study examining the relationship between gender expression and BMI in adolescence. Our findings indicate that socially assigned gender expression is a powerful predictor of BMI.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, gender nonconformity among sexual minority youth may elicit homophobic victimization, which may then mediate negative health outcomes and behaviors (eg, depression or maladaptive coping). 21,[34][35][36] In the current study, The denominators used to calculate percentages for age-specifi c prevalence vary because of the repeated-measures design and missing data on survey waves. The number of participants and repeated-measures observations refer to the data included in the analysis sample.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Health behaviors, especially those related to appearance, may be a way of embodying or establishing adherence to gender norms. 17,20,21 Because appearance ideals for girls and women center on thinness, whereas appearance ideals for boys and men focus on muscularity, the likelihood of using products to modify weight, shape, or appearance may be associated with overall gender differences in conformity to femininity and masculinity norms. [22][23][24] Laxative use to maintain or lose weight, particularly among girls and women, may be connected to greater conformity to appearance norms associated with femininity, and muscle-building product use, particularly among boys and men, may be connected to greater conformity to appearance norms associated with masculinity.…”
mentioning
confidence: 99%